Revolution in the echo chamber : audio drama's past, present and future - McMurtry, Leslie Grace (Intellect, 2019)
Revolution in the Echo Chamber is a sociohistorical analysis of British and US radio and audio drama from 1919 to the present day. This volume examines the aesthetic, cultural and technical elements of audio drama along with its context within the literary canon. In addition to the form and development of aural drama, Leslie Grace McMurtry provides an exploration of mental imagery generation in relation to its reception and production. Building on historical analysis, Revolution in the Echo Chamber provides contemporary perspective, drawing on trends from the current audio drama environment to analyse how people listen to audio drama, including podcast drama, today - and how they might listen in the future.